АКТУАЛЬНІ ПИТАННЯ ВДОСКОНАЛЕННЯ ІНСТРУМЕНТ АЛЬНОЇ ПІДГОТОВКИ МАЙБУТНЬОГО ВЧИТЕЛЯ МУЗИКИ (ГІТАРИСТА) (Педагогіка вищої та середньої школи, 2007)
The article investigates the questions of students’ preparing in the course of main musical instrument, particularly guitar through the contemporary musical and teaching tendencies.